Do Macroeconomic Factors and Mining Commodity Prices Affect the Mutual Fund Industry? Comparative Evidence of 3 Economic Periods - Lukita, Austin Ratna; Makarim, Zaki Anwar; Amalia, Adinda Maulida; Nugraha, Handy (International Journal of Science and Society, 2025)
This study aims to look at the effect of mining commodity prices and macroeconomic variables on the mutual fund industry in Indonesia with a comparison of 3 different economic periods. Background: Indonesia is known as one of the countries with the largest mining reserves in the world. This potential makes Indonesia one of the countries that is a strategic place to invest. However, in recent years there has been global economic turmoil that has a direct impact on investment, such as the US-China trade war, the COVID-19 pandemic, and the Russia-Ukraine war. Based on these events, the question arises whether mining price fluctuations and macroeconomic variables can affect mutual fund investment in Indonesia. Novelty: To the best of the researchers' knowledge, there has been no research linking nickel and copper commodity price variables to the mutual fund industry as well as research using a comparison of 3 economic periods. Research Methods: This research uses time series data analysis with the observation period 2013-2023 and the VECM (Vector Error Correction Model) method with three times of data analysis. This research is based on the utilization of secondary data types obtained from legitimate official Indonesian government institutions (Bank Indonesia, Financial Services Authority, and Central Statistics Agency) and investing.id website. Findings/Results: This study found that macroeconomic variables and mining commodity prices have different short-term and long-term effects on the mutual fund industry in Indonesia. Conclusion: The inconsistency of the variables affecting the mutual fund industry is caused by shocks that occur in different economic periods.